klasifikasi Klasifikasi frasa pada nama UMKM jajanan kaki lima di Gor Haji Agus Salim Padang - Sel Sunita; Afrini rahmi; Titiek Fujita Yusandra (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The use of phrases in the naming of street food SMEs in Gor Haji Agus Salim Padang can add to the attraction of visitors. This is because the use of the phrase gives a different impression to the given name. This study aims to determine the classification and structure of the phrase in the name of the UMKM street snacks in Gor Haji Agus Salim Padang after being analyzed from a syntactic point of view. This type of research is a qualitative research with a descriptive approach. The research data is in the form of words or sentences on behalf of hawker SMEs in Gor Haji Agus Salim. The source of the research data is the name of the hawker SMEs in Gor Haji Agus Salim. Based on the results of the study, it can be concluded that the classification of phrases based on the type of word in the name of the UMKM street snacks in Gor Haji Agus Salim is, First. noun phrases as many as 55 data. Second, verb phrases as much as 4 data. Third, the adjective phrase as much as 4 data. Fourth, the numeral phrase contains 2 data. Based on the relationship in the structure found, namely the type of attributive endocentric phrase, there are 4 data. The phrase structure found in this research is a phrase structure in the form of noun + noun, noun + verb, noun + adjective, noun + numeralia, noun + description, noun + number, and verb + description.